Mechanism of antigenic variation in an individual epitope on influenza virus N9 neuraminidase. - Air, G M (1990)
Monoclonal antibodies which inhibit influenza virus neuraminidase (NA) and which therefore indirectly neutralize virus infectivity bind to epitopes located on the rim of the active-site crater. The three-dimensional structure of one of these epitopes, recognized by monoclonal antibody NC41, has previously been determined (W. R. Tulip, J. N. Varghese, R. G. Webster, G. M. Air, W. G. Laver, and P. M. Colman, Cold Spring Harbor Symp. Quant. Biol. 54:257-263, 1989). Nineteen escape mutants of influenza virus A/tern/Australia/G70c/75 (N9) NA selected with NC41 were sequenced. A surprising restriction was seen in the sequence changes involved. Ten mutants had a Ser-to-Phe change at amino acid 372, and six others had mutations at position 367. No escape mutants with changes at 369 or 370 were found, although these mutations were selected with other antibodies and rendered the epitope unrecognizable by antibody NC41. Another N9 NA, from A/ruddy turnstone/NJ/85, which differs by 14 amino acids from the tern virus NA, still bound antibody NC41. Epitope mapping by selecting multiple escape mutants with antibody NC41 thus identified only three of the five polypeptide loops on NA that contact the antibody. Escape mutants selected sequentially with three different monoclonal antibodies showed three sequence changes in two loops of the NC41 epitope. The multiple mutants were indistinguishable from wild-type virus by using polyclonal rabbit antiserum in double immunodiffusion tests, but NA inhibition titers were fourfold lower. The results suggest that although the NC41 epitope contains 22 amino acids, only a few of these are so critical to the interaction with antibody that a single sequence change allows selection of an escape mutant. In that case, the variety of amino acid sequence changes which can lead to polyclonal selection of new epidemic viruses during antigenic drift might be very limited.